Optimal hedging of asian options - He, Shu. (2010)
The Black-Scholes option pricing model (1973) illustrates the modern theories of option valuation and hedging strategy. Black and Scholes used geometric Brownian motion to model stock price dynamics and proposed a delta-neutral hedging portfolio. The Black-Sholes model is based on the concepts of risk-neutral measure, stochastic calculus and no arbitrage principle. Solving the Black-Scholes partial differential equation gives rise to the Black-Scholes model for pricing European-style options.